Batas Dunia Tanpa Batas: Telaah Singkat Pemikiran I Made Andi Arsana - Eko Rangga Maulana (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this research is to find out the perspective of I Made Andi Arsana from the TEDxUGM youtube channel entitled